The relationship between game success indicators in the FIFA World Cup - Qatar 2022: An elastic-net regularization approach - Myftiu, A.; Thaqi, A. (Pedagogy of Physical Culture and Sports, 2023)
Background and Study Aim. The significance of analyzing statistical indicators is paramount, as they provide valuable insights into the distinguishing performance factors of teams. The purpose of this study: 1) to identify statistically significant differences between relevant performance factors among winning, drawing, and losing teams in the 2022 Football World Cup in Qatar; 2) explore indicators that are most strongly associated with the game results in this tournament.